ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI SEMANGKA DI DESA MARANATHA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Juprin, Fitriyani (AGROTEKBIS, 2016)
MaranathaÂ villageÂ is one ofÂ theÂ villages in the subdistrictÂ of sigi biromaru having productionÂ ofÂ watermelonÂ isÂ large enough. The size of the productionÂ ofÂ watermelonÂ does not yet guarantee a high income are accepted by farmers. ProductionÂ ofÂ watermelon obtained in the vilage maranatha relativeli hight, does not mean the income is also hight, so that required a research analisis income and feasibility farmingÂ of watermelon in the villageÂ ofÂ maranatha. Research aims to knowÂ the income and feasibility farmingÂ of watermelon that was held in july until september 2015. The determination of locationsÂ have done by deliberately (purposive) with consideration that the village of maranatha is one ofÂ producer watermelonÂ area with the productivity 2,85ton/ha. The analysis used in this research wasÂ incomeÂ analysisÂ (Ï) and feasibility (a). The result of the analysis showed that the average income of watermelonÂ farmersÂ for one growing season in the village of maranathaÂ isÂ Rp.16,045,618.06/1,02/ha mt or usd 15.730.998,1/ha/one growing season. The analysis showed revenue of cost ratioÂ was 3,31, thus, watermelon farm in the village of maranatha worthÂ to beÂ the efforted, because the volueÂ ratio>1.